Small mammals of the suburban areas of Warsaw in the diet of the tawny owl Strix aluco - Romanowski, Jerzy; Lesiński, Grzegorz; Bardzińska, Marta (Studia Ecologiae et Bioethicae, 2020)
We investigated the composition of small mammals at nine locations in the southwestern suburban zone of Warsaw (central Poland) through the analysis of the pellets of the Tawny owl Strix aluco. In total, we recorded 611 individuals of 15 species of small mammal communities in the diet. Rodents constituted the most numerous mammalian order. Among the most abundant prey we recorded were Myodes glareolus (63 individuals = 10.3% of all mammals), Apodemus agrarius (56 individuals = 9.2%) (173), Apodemus flavicollis (54 individuals = 8.8%), Mus musculus (48 individuals = 7.9%) and Microtus arvalis (44 individuals = 7.2%). We recorded also some species rarely captured by the tawny owl: Nyctalus noctula and Mustela nivalis. Species composition of small mammals of the study area resembled city parks, with several species typical for anthropogenic landscape.